1996
DOI: 10.3382/ps.0750900
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic and Cardiac Oxidative Stress and Other Metabolic Changes in Broilers with the Ascites Syndrome

Abstract: The objective of this study was to evaluate the gluconeogenic response of in vitro stimulated hepatocytes from control broilers and broilers with clinical manifestations of the ascites syndrome. The basal rate of glucose synthesis from lactate was found to be threefold greater in sick birds than in the control group and stimulation obtained with epinephrine was found to be quantitatively similar in both groups. Under basal conditions, the hepatocytes from the sick broilers exhibited 60% more ammonium than the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Indeed, oxidative injury with increased blood MDA content (Ozkan et al, 2007) and decreased anti-oxidative enzyme activity (Aksit et al, 2008) were involved in ascites or PHS broilers. It was also documented that broilers at risk of developing ascites syndrome showed oxidative damage in the heart, liver and lung Diaz-Cruz et al, 1996). Supplementation of anti-oxidants such as vitamin E, vitamin C, thioctic acid and selenium can ameliorate oxidative stress and reduce ascites or PHS related mortality Diaz-Cruz et al, 2003;Pan et al, 2005;Aksit et al, 2008).…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, oxidative injury with increased blood MDA content (Ozkan et al, 2007) and decreased anti-oxidative enzyme activity (Aksit et al, 2008) were involved in ascites or PHS broilers. It was also documented that broilers at risk of developing ascites syndrome showed oxidative damage in the heart, liver and lung Diaz-Cruz et al, 1996). Supplementation of anti-oxidants such as vitamin E, vitamin C, thioctic acid and selenium can ameliorate oxidative stress and reduce ascites or PHS related mortality Diaz-Cruz et al, 2003;Pan et al, 2005;Aksit et al, 2008).…”
Section: Discussionmentioning
confidence: 92%
“…Subsequent studies reported that vitamin E pellets implanted under the skin were effective in lowering ascites mortality in broilers, apparently by attenuating the processes leading to lipid peroxidation . Diaz-Cruz et al (1996) found that liver cells from broilers exhibiting ascites syndrome presented changes that were compatible with those observed in cases of oxidative stress. Bottje et al (1998) reported that the presence of oxidized glutathione in the lung lining¯uid of broilers was positively correlated with right ventricle:total ventricle weight ratios.…”
Section: Effect Of Cellular Damagementioning
confidence: 57%
“…The central etiology of AS is a hypoxemic condition (hypoxemia refers to blood in the systemic arteries that is under saturated with oxygen; Wideman et al, 2013) resulting from an imbalance between demand and supply of oxygen (Kalmar et al, 2013). Bakonyi & Radak (2004) reported that exposure to high altitude increases the formation of reactive oxygen species (ROS) and reactive nitrogen species, and ROS cause lipid peroxidation in heart and liver of broilers (Díaz-Cruz et al, 1996). Bottje et al (1995) reported that oxidative stress is associated with AS.…”
Section: Introductionmentioning
confidence: 99%